Paracoccidioidomycosis: an uncommon clinical presentation, - Bruno Augusto Alvares; Cláudia Alves Lapa Gracia; Mariangela Esther Alencar Marques; Silvio Alencar Marques
Abstract Paracoccidoiomycosis is a systemic mycosis with a higher incidence in males with history of exposure to the rural environment; its classic clinical manifestation is an oro-pulmonary lesion. The authors report a case of a female, urban, 76-year-old patient with atypical clinical-dermatological presentation and diagnostic conclusion after histopathological examination. The clinical response was quick and complete after treatment with itraconazole 400 mg/day in the first month, decreased to 200 mg/day until the sixth month of treatment.